CORRELATION ANALYSIS OF ACCUMULATION AMONG DIFFERENT CHEMICAL ELEMENTS IN BULBS OF WINTER GARLIC (ALLIUM SATIVUM L.) - T. M. Seredin; L. I. Gerasimova; E. G. Kozar; A. F. Agafonov; A. V. Soldatenko; L. V. Krivenkov (Овощи России, 2017)
Winter garlic as a source of vitally necessary macro and microelements is very important in human's diet. Therefore, correlation links among accumulation the basic chemical elements in bulbs of winter garlic were estimated. It was shown that positive reliable relationship (r=0.71-0.85) was discovered between average potassium accumulation and elements, such as magnesium, aluminum and boron, and also between magnesium and boron accumulation, and between aluminum and magnesium. The correlation analysis showed negative relationship between cadmium accumulation with copper (r=-0.71) and silicon (r=- 0.66) accumulations. There is no significant relationship between lead accumulation and other element accumulation. The significant positive correlation was revealed between accumulation of radionuclides 90Sr, 137Cs in garlic bulbs and accumulations of aluminum, calcium, boron and magnesium with coefficients 0.74 and 0.85; 0.70 and 0.78; 0.65 and 0.77; 0.57 and 0.72, respectively. It was shown that accessions more resistant to diseases accumulated less cadmium (r=-0.47), but more lead (r=0.49). Moreover, it was noticed that accessions with high accumulation of potassium had the low percent of well-wintered bulbs (r=-0.57), but more accumulation of Zn and Fe caused the improved hardiness (r=0.80, 0.75, respectively).